2011
DOI: 10.1007/s00540-011-1227-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunct intrathecal magnesium sulfate to bupivacaine for spinal anesthesia: a randomized, double-blind trial in patients undergoing lower extremity surgery

Abstract: In patients undergoing lower extremity surgery with spinal anesthesia, the addition of 100 mg IT MgSO(4) to 15 mg bupivacaine without opioid supplement, prolonged the duration of the sensory block, decreased postoperative analgesic consumption, and significantly prolonged the onset of spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
10
54
0
1
Order By: Relevance
“…The incidence of adverse events (hypotension, pruritis) were insignificant with intrathecal magnesium. This was consistent with the results of other studies (20,21,22,23) Mitrajabalameli and Seyed Hamid Pakzadmoghadam et al compared effects of adding different doses of intrathecal magnesium sulfate for spinal anesthesia in the cesarean section and showed that all doses studied provide safe and effective anesthesia, but 75 mg of this drug increases duration of postoperative analgesia and prolong than sensory and motor block without significant increase in maternal and neonatal side effects (20).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The incidence of adverse events (hypotension, pruritis) were insignificant with intrathecal magnesium. This was consistent with the results of other studies (20,21,22,23) Mitrajabalameli and Seyed Hamid Pakzadmoghadam et al compared effects of adding different doses of intrathecal magnesium sulfate for spinal anesthesia in the cesarean section and showed that all doses studied provide safe and effective anesthesia, but 75 mg of this drug increases duration of postoperative analgesia and prolong than sensory and motor block without significant increase in maternal and neonatal side effects (20).…”
Section: Discussionsupporting
confidence: 89%
“…Magnesium exerts its analgesic action as a non-competitive NMDA receptor antagonist, blocking ion channels in a voltage dependent manner (20,21,22) .This drug is both analgesic and anti -nociceptive additive drug. When used with local anaesthetic, it resulted in prolongation of analgesia without significant complication (23,24).This prolongation of anaesthesia is consistent with the experimental synergistic action between spinal local aneasthetic and NMDA antagonists like magnesium sulphate, which use anti -nociceptive effects via different mechanisms; (25,26,27) hence the rationale for combining the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] In two studies 17,18 addition of different doses of intrathecal magnesium sulphate to hyperbaric bupivacaine was studied where as in a study 19 fentanyl was also used as adjuvant. Magnesium sulphate 100 mg as adjuvant to bupivacaine and saline was compared in another study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Khalili G and Janghorbini et al, 15 who compared Magnesium Sulphate with Bupivacaine Vs. plain Bupivacaine for lower extremity surgeries concluded that the duration of sensory blockade was significantly longer with Magnesium Sulphate group than in control group (magnesium sulphate 106.5 min. vs. control group 85.5 min., p<0.001), similar to our study.…”
Section: Discussionmentioning
confidence: 99%